Efficacy of per operative use of powdered vancomycin in reduction of early post-operative superficial surgical site infection in single level prolapsed lumber intervertebral disc surgery - Ahmmed, Tayeb; Chowdhury, Dhiman; Fatima, Kanij; Razib, K. Olinur; Islam, Kazi Saiful; Rahim, M. Abdur; Islam, Muhammad Saiful; Zaman, Mariam; Joarder, Ariful Islam; Raihan, Farid; Bari, Mohammad Shahnawaz (International Journal of Research in Medical Sciences, 2024)
Background: Decompression (fenestration and discectomy) of lumber disc herniation is one of the most common surgical procedures done by neurosurgeons. The aim of this study was to evaluate the efficacy of per operative use of powdered vancomycin in reduction of early post-operative superficial surgical site infection in single level prolapsed lumber intervertebral disc surgery. Methods: This was a Quasi-experimental type of study carried out in the Department of Neurosurgery, Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh from October 2022 to September 2023. Results: In this study, the mean age was 42.2±10.5 years, ranging from 20 to 60 years. The highest incidence of prolapsed lumbar intervertebral disc (PLID) was in the vancomycin group among patients aged 41-60, with a male-to-female ratio of 1.7:1. Most PLID cases (59.4%) occurred at the L4/5 level. Out of 32 patients, only four (no vancomycin group) had an ESR above 75 mm/hr. On the 30th postoperative day, significantly increased CRP levels and signs of infection were observed. Among those with purulent discharge, 50% had Staphylococcus aureus, 25% had Staphylococcus epidermidis, and 25% showed no pathogen growth. Conclusions: In this study, we found that there is a significant effect of topical application of powdered vancomycin in addition to systemic antibiotic prophylaxis over the subcutaneous tissue following fenestration and discectomy in single level prolapsed lumber intervertebral disc and reduction in the incidence of superficial surgical site infection.